Conformation and Orientation of the Retinyl Chromophore in Rhodopsin: A Critical Evaluation of Recent NMR Data on the Basis of Theoretical Calculations Results in a Minimum Energy Structure Consistent with All Experimental Data - Singh, Deepak; Hudson, Bruce S; Middleton, Chris; Birge, Robert R (Biochemistry (Easton), 2001)
In the absence of a high-resolution diffraction structure, the orientation and conformation of the protonated Schiffs base retinylidinium chromophore of rhodopsin within the opsin matrix has been the subject of much speculation. There have been two recent reliable and precise NMR results that bear on this issue. One involves a determination of the C20−C10 and C20−C11 distances by Verdegem et al. [Biochemistry 38, 11316−11324 (1999)]. The other is the determination of the orientation of the methine C to methyl group vectors C5−C18, C9−C19, and C13−C20 relative to the membrane normal by Gröbner et al. [Nature 405 (6788), 810−813 (2000)]. Using molecular orbital methods that include extensive configuration interaction, we have determined what we propose to be the minimum energy conformation of this chromophore. The above NMR results permit us to check this structure in the C10−C11C12−C13 region and then to check the global structure via the relative orientation of the three C18, C19, and C20 methyl groups. This method provides a detailed structure and also the orientation for the retinyl chromophore relative to the membrane normal and argues strongly that the protein does not appreciably alter the chromophore geometry from its minimum energy configuration that is nearly planar s-trans at the 6−7 bond. Finally, the chromophore structure and orientation presented in the recently published X-ray diffraction structure is compared with our proposed structure and with the deuterium NMR results.